Analisis Pemanfaatan Dana Pensiun dalam Pemenuhan Kebutuhan Hidup Pensiunan PNS di Kabupaten Belu - Nolviana Arisa Bete; Nikson Tameno; Cicilia A. Tungga (Universitas Veteran Bangun Nusantara, 2024)
The research aims to analyze how the use of pension funds affects the daily lives of retired civil servants and the excent to which pension funds have been utilized optimally according to their needs. The research method used is qualitative with a case study approach, involving in-depth interviews with retired civil servants and analysis of related pension policy documents. The research results show that the use of pension fundshas a significant impact on the financial literacy, invesment strategies and financial planning influence the effectiveness of using pension funds. This research also illustrates that the majority of retired civil servants in Belu regency are able to utilize pension funds optimally according to their living needs, althoungh challenges such as inflation and the ever-increasing cost of living are still a major concern. This study is expected to provide deeper insight into how pension fund management can be improved to improve the quality of live of retired civil servants in retirement, as well as provide recommendations for better policies in managing pension funds in Belu Regency.